2004
DOI: 10.1108/09540910410537336
|View full text |Cite
|
Sign up to set email alerts
|

Reliability testing and data analysis of lead‐free solder joints for high‐density packages

Abstract: Temperature cycling tests, and statistical analysis of the results, for various high‐density packages on printed‐circuit boards with Sn‐Cu hot‐air solder levelling, electroless nickel‐immersion gold, and organic solder preservative finishes are investigated in this study. Emphasis is placed on the determination of the life distribution and reliability of the lead‐free solder joints of these high‐density package assemblies while they are subjected to temperature cycling conditions. A data acquisition system, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…This result implies that the reliability of SnAgCu alloys outperform SnPb for small components and vice versa for large components. This conclusion is consistent with the thermal fatigue experimental results that suggested that SnAgCu alloys outperform SnPb at low strain applications and vice versa at high-strain amplitude applications [14][15][16][17][18][19]. Figure 10.…”
Section: Effect Of Thermal Shocksupporting
confidence: 81%
“…This result implies that the reliability of SnAgCu alloys outperform SnPb for small components and vice versa for large components. This conclusion is consistent with the thermal fatigue experimental results that suggested that SnAgCu alloys outperform SnPb at low strain applications and vice versa at high-strain amplitude applications [14][15][16][17][18][19]. Figure 10.…”
Section: Effect Of Thermal Shocksupporting
confidence: 81%
“…al. [50] reported there were no solder joint failures on the lead-free balled flexBGA with both SnAgCu and SnPb solder pastes on all the SnCu HASL, Ni-Au, and OSP PCBs during temperature cycles from 0 to 100°C for 6,000 cycles.…”
Section: Experimental Results On Bga Packagesmentioning
confidence: 99%
“…al. [50] reported the test results for the Ceramic Column Grid Array (CCGA) packages with both SnAgCu and SnPb solder paste on PCBs with three finishes: Sn-Cu HASL, Ni-Au, and OSP. They found failures on all the three PCBs with SnAgCu, but no failures with SnPb solder paste.…”
Section: Experimental Results On Bga Packagesmentioning
confidence: 99%
“…Though more voids were observed in forward compatibility assemblies for BGAs/CSPs [1], the reliability of forward compatibility assemblies is equivalent or better than the reliability of the SnPb balled BGAs with SnPb solder paste [2,25,32].…”
Section: Forward Compatibilitymentioning
confidence: 99%
“…This included lead-free SnAgCu paste with tin-lead CSP169, CSP208, PBGA256, CBGA256 and 2512 chip resistors. Lau et al concluded that the quality of the SnPb balled FLEXBGA solder joints with lead-free solder paste on Ni-Au PCB is better than that with SnPb solder paste on an OSP PCB with 99 percent confidence level [32]. Note that all studies in forward compatibility assembly used SnAgCu reflow profiles.…”
Section: Forward Compatibilitymentioning
confidence: 99%